Improvement of existing public office buildings in Nigeria from users’ perspective using lean thinking – a pictorial view - Adeyemi, Adegbenga; Martin, David; Kasim, Rozilah (Islamic Azad University, 2016)
This paper gives a pictorial view of the relevance of lean thinking, particularly the application of muda as a supplement to the sustainable improvement diagnosis technique of existing public office buildings, for a fuller assessment of users’ requirement in Nigeria. The impact of perceived muda was related to the triple bottom line of sustainable development on perceived job productivity and design features and estimated from end-users’ perspective, using diagnostic POE as data acquiring tool, while the confirmatory analysis was done through AMOS, SPSS and MS Excel to explain the relationship between the different variables. The findings showed that muda is inherent in public office buildings and it has highly significant causal effects of 0.66 and 0.76 respectively on perceived job productivity and design features; it also has strong effect sizes of 44% and 58% in explaining both their variances respectively. The result revealed that users require more improvement in facilities as against spatial plan and structures, while there is a medium and positive correlation of 0.48 between perceived job productivity and design features – implying that improvement in design features will consequently lead to improvement in perceived job productivity. The study concludes that lean thinking is relevant to building improvement and could serve as good supplement to the current improvement diagnosis of existing public office buildings, but not as a substitute since data were only collected from users who are not able to provide the required technical data that would otherwise warrant use of equipment.